Gender-responsive budgeting: Assessment of implementation, impact and challenges in Serbia : DOI: 10.5937/etp2404099k - Kosorić, Danko (Ekonomija - teorija i praksa, 2025)
Gender-responsive budgeting is a key strategy for promoting gender equality and fair distribution of resources in society. The implementation of this concept in the Republic of Serbia faces numerous challenges, but at the same time it has the potential to significantly influence the improvement of the position of women and other vulnerable groups. This overview paper aims to analyze the current situation in the Republic of Serbia when it comes to the implementation, impact and challenges of gender-responsive budgeting. The research aims to identify key goals, analyze the achieved results, as well as identify obstacles and recommendations for the improvement of this area. Through a comprehensive analysis, the work will contribute to a better understanding of the importance of gender-responsive budgeting in the Republic of Serbia and suggest steps towards improving this area in the future.